Kegiatan Pengabdian Masyarakat Terhadap Deteksi Dini Gangguan Perilaku, Emosional, dan Psikososial Di Sekolah Dasar Negeri 01 Ciherang - Fransisca Iriani R Dewi; Trinatalis Gulo; Lita Eka Wulandari; Nayra Fitrianita Efna; Kalya Sukma Ramadhani; Edward Bellarmino; Budianto, Gabriel Arnold; Alexander Halim Santoso (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Behavioral and emotional problems among children and adolescents, commonly referred to as mental health problems, often result in significant functional impairment. This research uses the PDCA (plan-do-check-action) method. The aim of this research is to carry out early detection of children's behavioral, emotional and psychosocial problems. It is hoped that this can increase insight and create behavior for further evaluation, so as to avoid the negative impact of behavioral, emotional and psychosocial disorders